Effect of Crack on Bending Process for S55c Carbon Steel with Ultrasonic Testing on Zero Degree Probes - Ali K.; Rifai D.; Siaw Paw J.K.; Abdalla A.N.; Hen C.K.; Sukor M.F.M.; Ismail Z.; Ding T.J. (Institute of Physics Publishing, 2023)
Cracks; Fatigue of materials; Plates (structural components); Probes; Steel testing; Ultrasonic testing; Acoustic emission techniques; Bending force; Bending process; Crack monitoring; Excitation frequency; Failure points; Fatigue cracks; Original design; Acoustic emission testing